Aporias na conservação-restauração de pinturas concretas brasileiras - Giulia Villela Giovani (2020)
The study here presented is based on the analysis of different conservationrestoration processes in which concrete Brazilian paintings were submitted, especially those produced in the 1950s. The objective is to analyze the diverse strategies of preservation, approaching an extended discussion about the point of view of the theory, and its developments in the field in question. The research aims to instigate reflections about the processes of the conservation-restoration field, critically evaluating the guidelines of the restorative and the preventive conservation practices, the discursive-project ellaboration that proceed or justify them, and the results of the procedures carried out. The thesis is based on the study of the artworks by artists covered in the project Concrete Art in Brazil: ndustrialism and Latin American avant-garde, made through documentary research, interviews, analysis of techniques and materials, the conservation state, and other methodologies. The observations and information collected were evaluated and it was found that most of these works have been through conservation-restoration interventions. In this sense, this study proposes an analysis of the accomplished interventions, highlighting the aporias, as well as dialogisms – dialogue between different parts, not always aligned – presented in this field of knowledge in order to raise the question and the need for an expanded reflection on the topic. The work in question has as one of its greatest intents to remedy the lack of work that devotes itself to theorize about restorative procedures of modern artworks. Above all, since in evoking material and aesthetic issues other than those offered by works linked to the previous tradition of the medium, those objects demand the creation of an updated reflection about their preservation. Since, in the case of preservation, the technical and scientific means are tools that corroborate the execution guided by theoretical assumptions, these data are used first in discussion or in the truly theorizing reflection, only in the investigation, in this sense, would be ineffective. It remains for the study to measure itself with the dictates ordering history, criticism, and history of art; in addition to other elucubrations from the social and human sciences - responsible for the way of the appreciation and election of aesthetic, artistic, historical values, among other factors.